Expression of Adhesion Molecules in Synovia of Patients with Treatment-Resistant Lyme Arthritis - Akin, Evren (American Society for Microbiology, 2001)
The expression of adhesion molecules in synovium in patients with Lyme arthritis is surely critical in the control of Borrelia burgdorferi infection but may also have pathologic consequences. For example, molecular mimicry between a dominant T-cell epitope of B. burgdorferi outer surface protein A and an adhesion molecule, human lymphocyte function-associated antigen 1 (LFA-1), has been implicated in the pathogenesis of treatment-resistant Lyme arthritis. Using immunohistochemical methods, we examined synovial samples for expression of adhesion molecules in 29 patients with treatment-resistant Lyme arthritis and in 15 patients with rheumatoid arthritis or chronic inflammatory monoarthritis. In Lyme arthritis synovia, endothelial cells showed intense expression of P-selectin and vascular adhesion protein-1 (VAP-1). Expression of LFA-1 was also intense on infiltrating cells, particularly in lymphoid aggregates, and intercellular adhesion molecule-1 (ICAM-1) was markedly expressed on synovial lining and endothelial and infiltrating cells. Moderate expression of vascular cell adhesion molecule-1 (VCAM-1) was seen on synovial lining and endothelial cells, and mild expression of its ligand, very late antigen-4, was apparent in perivascular lymphoid infiltrates. Except for lesser expression of VCAM-1 in Lyme synovia, the levels of expression of these adhesion molecules were similar in the three patient groups. We conclude that certain adhesion molecules, including ICAM-1 and LFA-1, are expressed intensely in the synovia of patients with Lyme arthritis. Upregulation of LFA-1 on lymphocytes in this lesion may be critical in the pathogenesis of treatment-resistant Lyme arthritis.